RESEARCH OF THE INFLUENCE OF IMPURITIES DYSPROSIUM AND THULIUM ON THE LUMINESCENCE OF SOLID SOLUTIONS Y1– xYb x Al3(BO3)4 - Sergey Vladimirovich Kostyukov (Вестник Северо-Кавказского федерального университета)
Has established the dependence of the intensity of IR-luminescence of polydisperce solid solutions Y1–xYbxAl3(BO3)4 on the ion concentration of dysprosium and thulium. Has offered the mechanisms of energy transfer between the ytterbium ions and impurity ions.